Influence of planting and harvest time on productivity of sweet potato varieties in the Baixada Fluminense - Menezes, Dinah Mochel de; Cezar, Terezinha Iza; Carvalho, Jefferson Ferreira de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this experiment was to study the response of four sweet potato varieties to date of planting and harvest in the Baixada Fluminense, Rio de Janeiro. In each of three years, 1969-1972, plantings were made in each of the four seasons (spring, summer, fall, and winter). The varieties used were Moranguinha (No. 10-SCA), Amendoim (No. 25-SCA), Salmon (No. 6-SCA), and No. 35-SCA. Two different harvest dates were utilized - six months and eight months after planting. The following yields were obtained from the four varieties: Amendoim - 8,270 kg/ha; No. 35-SCA - 7,786 kg/ha; Moranguinha - 7,730 kg/ha; Salmon - 5,658 kg/ha. The fall plantings were higher yielding in 1969/70 and 1971/72, with average yields of 10,557 and 9,608 kg/ha, respectively. In 1970/71, however, there were no significant differences among yields from the four different planting dates. Maximum yield of 8,150 kg/ha was obtained from the eight months after planting harvest date. This yield was 24% higher than the yield obtained from the six months after planting harvest date. The highest yield from the experiment (averaged over three years) was from the variety Moranguinha, planted in the fall, which yielded 11,988 kg/ha.